Praktik Pembayaran Upah Pada Penjahit Uli Kota Bengkulu Berdasarkan Persepektif Ekonomi Islam - Lestari, Sri; Isnaini, Desi; Hasanah, Uswatun (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
This research was conducted at Penjahit Uli in Bengkulu City using a qualitative method. The informants included business owners and 10 customers of Penjahit Uli in Bengkulu City, selected based on their knowledge and experience related to the issues under investigation. Data were collected through interviews with informants as primary data, and from research references, books, journals, and hadiths as secondary data. The research findings indicate that wage payment practices at Penjahit Uli in Bengkulu City are done twice: an initial payment (down payment/DP) upon fabric delivery and full payment upon completion of the sewing. However, not all customers are aware of the wage amount initially because Penjahit Uli does not disclose it, and customers do not inquire about it. This is due to mutual trust between both parties. After the sewing is completed, Penjahit Uli determines the wage amount, and customers pay in full without negotiation. From the perspective of Islamic Economics, the wage payment practice at Penjahit Uli in Bengkulu City falls under ijarah al-a’mal. This practice complies with general provisions, specifically number seven, regarding ijarah al-a’mal as stated in the fatwa DSN-MUI, NO.12/DSN-MUI/IX/2017. Furthermore, the wage provided is deemed appropriate, meets needs, is fair, and adheres to the agreed-upon timeframe.